Коаксиальный термометрический мост с эквипотенциальной защитой - Мелещук, Д.В.; Михаль, А.А.; Варша, З.Л. (Технічна електродинаміка, 2014)
Рассмотрена измерительная цепь термометрического коаксиального моста. Показана реализация в ней эквипотенциальной защиты токовой и потенциальной ветвей от токов утечки. В цепь после делителя напряжения включен промежуточный трансформатор, который создает режим заданного тока в объекте измерения и защитные потенциалы. Также в ней использован повторитель напряжения для уменьшения влияния сопротивления подводящих проводов на точность измерений и создания защитного напряжения в токовой ветви. Проведен анализ погрешности измерения, которая обусловлена наличием паразитных сопротивлений в токовой ветви и погрешностью повторителя напряжения. Показан результат уменьшения этой погрешности при использовании промежуточного трансформатора. Рассмотрена погрешность измерения, возникающая при наличии тока утечки, который шунтирует платиновый термопреобразователь сопротивления. Розглянуто вимірювальний ланцюг коаксіального моста. Показано реалізацію в ньому еквіпотенційного захисту струмової та потенціальної гілок від струмів витоку. В ланцюг після подільника напруги включено проміжний трансформатор, який створює режим заданого струму в об'єкті вимірювання та захисні потенціали. Також у ньому використовується повторювач напруги для зменшення впливу опору з'єднувальних дротів на точність вимірювань та створення захисної напруги в струмовій гілці. Проведено аналіз похибки вимірювання, що обумовлена наявністю паразитних опорів в струмовій гілці та похибкою повторювача напруги. Показано результат зменшення цієї похибки при використанні проміжного трансформатора. Розглянуто похибку вимірювання, що виникає при наявності струмів витоку крізь паразитну ємність вимірювального кабелю. For precision thermometry measurements transformer ac bridges are widely used. Pressing issue is to improve the accuracy of measurement on basis of structural methods. This article describes one of the methods that improves noise immunity of measuring chain device. The functional diagram of the measuring chain of thermometric bridge tested. It uses coaxial conductors to reduce the interaction of the magnetic and electrostatic fields in the measurement process. Connecting the measuring object is implemented by tri- axial cable. This provides an equipotential protection against leakage. There is an intermediate transformer in the measuring circuit after the voltage divider. It performs two main functions. First, it creates a constant-current mode to the measurement object. This is ensured by additional secondary winding. Secondly, it creates the necessary protective potentials. This is ensured by the fact that the secondary windings of the transformer are carried out by screened wire. In measuring chain the voltage follower inserted. It reduces resistance of the connecting wires impact to the measurement accuracy. It also creates voltage for equipotential protection in the current branch. The analysis of measurement error carried out, which is caused by the presence of parasitic resistances in the current branch and by the error of voltage follower. It may have a value greater than 10-6. The effect of reducing this error by using an intermediate transformer demonstrated. The error of measurement, which occurs in the presence of leakage current through the parasitic capacitance of the measuring cable, tested. It is shown that the error in measurement of reactive component of the object of measurement can be greater than 100 %. This error can change the sign of the phase shift of the object of measurement. As a result, the nature of the reactive component in the two-element equivalent circuit can be changed. Instead inductive type it will be capacitive. This will complicate the process of automatical balancing the quadrature component of the bridge. Equipotential protection can eliminate this problem.